The Study of Laban Movement Analysis (LMA) in Shadow Puppets Theatre - Abdul Ghani, Dahlan (Estudios sobre el Mensaje Periodístico, 2017)
The art of shadow play within the Malaysian Wayang Kulit is unique with rich articulated translucent shadow movement but unfortunately it is slowly dying. In the past, the movement of puppets and shadows are performed by the skilled and experienced puppeteers or ‘Tok Dalang’. Without realizing it that puppets movement are driven or influenced by human bodily motion. With the current scenario of shadow play is slowly being imminent extinct, we would like to discuss relationship between Laban Movement Analysis (LMA) in Wayang Kulit puppets movement. This research will focused on main areas that were identified in Wayang Kulit within LMA theory such as physical, space, shape, and effort. This research will hope that it will provide a tacit knowledge that LMA theory exist and applicable in shadow puppets or Wayang Kulit that would benefit for future research.